Lived Experience of Individuals with Dissociative Disorders: A Phenomenological Study - Nazari Kamal, Mina; Ahi, Qasem; Mansouri, Ahmad; Mehrabizadeh Honarmand, Mahnaz; Shahabizadeh, Fatemeh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aims to explore the disorder and the interrelations among its components from the perspective of individuals affected by it. Methods and Materials: This study is conducted by adopting an interpretivist philosophy, a qualitative approach, a phenomenological strategy, content analysis techniques, and in-depth interview tools. The study sample includes 12 individuals diagnosed with dissociative disorder, selected through purposive and convenient sampling until theoretical saturation was reached. Ultimately, the experiences of individuals with dissociative disorder indicate that this condition is fundamentally a traumatic disorder that profoundly affects the individual’s entire cognitive and functional system. Findings: Four key dimensions—personal characteristics, environmental conditions, personality disorder, and psychological disorder—not only constitute the essence of this disorder but also influence it significantly. Conclusion: This study highlights the complex interplay of personal, environmental, personality, and psychological factors in the development of dissociative disorders. It emphasizes the importance of integrated treatment approaches, combining clinical interventions with social and familial support for effective management.